Structural Origins of BaF2/Ba1 −xRxF2 +x/RF3 Nanocrystals Formation from Phase Separated Fluoroaluminosilicate Glass: A Molecular Dynamic Simulation Study. Issue 10 (1st July 2019) - Zhao, Junjie; Xu, Xiuxia; Ren, Kai; Luo, Zhou; Qiao, Xvsheng; Du, Jincheng; Qiu, Jianbei; Fan, Xianping; Qian, Guodong
Abstract: Fluoroaluminosilicate glass‐ceramics with M1 − x R x F2 + x (M 2+ : Sr 2+, Ba 2+, R 3+ : rare earth ions) crystals are novel host materials for luminescence applications. However, the preparation of such materials is still a trial‐error based approach due to the lack of detailed glass structure understanding. In this work, the authors study the phase separation and potential nanocrystal formation in a series of Ba 2+ and La 3+ containing fluoroaluminosilicate glasses by molecular dynamics (MD) simulations. Fluoride phase separation is observed from all simulated glass samples. With gradual LaF3 to BaF2 substitution, the cations enrichment changes from Ba 2+, to Ba 2+ and La 3+, and finally La 3+ in the fluoride‐rich regions. Besides, the competition between Al 3+ and La 3+ in fluoride phase and the consequently redistribution of Al 3+ and Na + into oxide phase are observed, which can change the local environment of luminescent centers, affecting luminescence. An experimental support to this phenomenon is given. Therefore, MD simulation with effective potentials can be a practical method to study the structural origins of nanocrystal from fluoride phase separation as well as to study the structure‐property relationship in fluoroaluminosilicate glass. The simulation driven glass structure and crystal phase exploration can thus become an effective method in designing glass‐ceramics for luminescence and other applications. Abstract : This paper uses molecular dynamics simulations to study the structure origins of BaF2 /Ba1 − x R x F2 + x /RF3 nanocrystals in fluoroaluminosilicate glass. Coupled with experiment validations, this paper also reveals the competition between R 3+ and Al 3+ in separated fluoride phase and the effects on luminescence of such competition. This study can help to explore novel oxyfluoride glass‐ceramics in the future.